2020
DOI: 10.3390/molecules25204732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strain, Wood Substrate and Cold Treatment on the Yield and β-Glucan Content of Ganoderma lucidum Fruiting Bodies

Abstract: Wood residues from forestry industries can be potential raw materials for specialty and edible mushroom production. The aim of this study was to evaluate the suitability of wood residues for the cultivation of Ganoderma lucidum originating from boreal forests. The substrates tested included sawdust and wood chips of Betula spp., Populus tremula, Picea abies, Pinus sylvestris and Larix sp. The suitability of the substrates and the ability of the strains to develop fruiting bodies and produce β-glucan were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…A statistical analysis of the total glucans content also revealed significantly higher values in all of the heat-treated samples than the control ( Figure 4 c). The β-glucan contents reported from Reishi or Ganoderma mushrooms were in a wide range of variability from as low as 4 g 100 g −1 to as high as 55.9 g 100 g −1 of dried materials [ 41 , 42 ]. This high range of deviation in the mentioned values can reflect the taxonomical confusion, improper identification, different growth condition, cultivation practices and the applied extraction methods and quantification techniques.…”
Section: Resultsmentioning
confidence: 99%
“…A statistical analysis of the total glucans content also revealed significantly higher values in all of the heat-treated samples than the control ( Figure 4 c). The β-glucan contents reported from Reishi or Ganoderma mushrooms were in a wide range of variability from as low as 4 g 100 g −1 to as high as 55.9 g 100 g −1 of dried materials [ 41 , 42 ]. This high range of deviation in the mentioned values can reflect the taxonomical confusion, improper identification, different growth condition, cultivation practices and the applied extraction methods and quantification techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid spawn obtained by submerging fermentation techniques can yield mycelial biomass and a more uniform mycelial biomass in a shorter period [ 26 ]. Sawdust and rice bran substrates are suitable for Polyporale species cultivation for linear growth and spawn production [ 12 , 27 , 28 ]. However, in contrast with earlier studies, oyster mushrooms cultivated on sawdust substrates have more recently been shown to demonstrate a low yield and biological efficacy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earthwormbased composting (vermicomposting) can decompose organic waste to produce odourless humus-like substances that are beneficial to the environment, according to the scientific literature in recent years [7][8][9][10]. Vermicomposting is a key biotechnological composting technology in which various earthworms are adapted to improve the waste conversion process [11][12][13][14], combining an advanced microbe technology with a vermicomposting approach, such as effective microorganism technology, can reduce the time required and shows the stability and maturity of the product.…”
Section: Strains Residues Referencesmentioning
confidence: 99%
“…Wheat straw, soybean straw or paddy, and other agricultural wastes are valuable residues of edible mushroom production described in Table 1. Mushroom substrates generate almost 1-2 tonnes of waste for every tonne of mushrooms collected [3] and are generally disposed of in landfills, which causes eutrophication of the surface water basins through nutrient leaching or composted after mushroom harvest [4] as well as commonly disposed of through open burning, producing airborne hazards [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%